An investigation into the environmental knowledge, attittudes and behavioural intentions of elementary school students - Amarant, Arlene (Curtin University, 2006)
This study was designed to find out elementary students knowledge about the environment, their attitudes towards helping the environment and what they actually have done to help the environment. Specifically, during the northern spring of 2002 all grade-4 and grade-5 students in one public elementary school in Miami-Dade County, Florida were administered the Children's Environmental Attitude and Knowledge Scale (CHEAKS) instrument. In 2002, some students in both grade levels interviewed each other in pairs to determine why they answered the way they did on the CHEAKS instrument. In the interviews, students discussed what they had been taught in school, compared to what they had learned outside of school that was related to the environment. The following year, during the northern spring of 2003, all grade-4 and grade-5 students in the same elementary school were given the CHEAKS instrument. Students at the elementary school were also asked questions which they answered in writing. These included: Which questions on the survey did you feel were difficult?; what do you remember learning about environmental education in school, at home or elsewhere? In addition, some gifted grade-6 students, who attended the nearby middle school and other grade-6 students who were in heterogeneous ability classes also responded to the CHEAKS instrument.Analysis of the data showed that grade-4 students in this elementary school had a higher commitment to the environment than did grade-5 students and gifted students had more knowledge than regular students. Only the gifted students in grade-5 had a high commitment to the environment. Comparing independent t-test results in year 2002 between grade-5 regular students (n=105) and grade-5 gifted students (n=30), grade-5 gifted students were statistically less committed to the environment in terms of scores on the Verbal Commitment. There was no difference in knowledge or commitment in grade-6 students. Girls were more verbally committed to the environment than boys. Having knowledge about the environment did not necessarily mean students were committed to saving the environment or took action to solve environmental problems. The thesis concludes with explanations, discussions about the limitations of the study and suggestions for further research.